Variations in Criminal Patterns Among Narcotic Addicts in Baltimore and New York City, 1983-1984 - Nurco, David N. ([Verlag nicht ermittelbar], 1991)
This data collection was undertaken to develop a typology of narcotic addicts according to the kind, frequency, and seriousness of their crimes and to identify the most serious criminal offenders, thereby determining which individuals were best suited to rehabilitation. The following questions are addressed by the data: (1) What "types" of narcotic addicts can be distinguished in terms of their criminal behavior? Which of these types are amenable to rehabilitation? (2) At what time during their addiction careers do addicts commit the most crime? Do narcotic addicts "mature" out of addiction? (3) What is the relationship between individuals' involvement in crime prior to addiction and their criminal activity and drug use over their addiction career? (4) Which demographic, personality, or other factors are associated with serious crime committed during periods of narcotic addiction? (5) What are the contributions of situational and dispositional factors to the relationship between addiction and crime? Part 1 of the collection details the subjects' addiction careers, the age they first used various drugs, the age they first became addicted to narcotics, the amount of time they were addicted/not addicted to narcotics, and the total length of their addiction careers. Part 2 contains variables generated by cluster analysis, including cluster assignment or "type." Part 3 includes the educational, occupational, and arrest histories of the subjects, as well as the drug use and arrest histories of their families. The Part 4 file consists of Minnesota Multiphasic Personality Inventory and Raven Progressive Matrix scores. The frequency and types of crime that subjects committed during the preaddiction period comprise Part 5, while the frequency and nature of drug use during the preaddiction period comprise Part 6. Parts 7 and 8 contain crime variables and drug use variables, respectively, across all nonaddiction periods. Finally, Part 9 contains data characterizing crime across all addiction periods, and Part 10 contains variables regarding drug use across total addiction periods.